Optimizing The Use of Social Media and The Importance of Financial Management For Smes/Smes In Pematang Siantar City - Darwin Lie; Nana Triapnita Nainggolan; Lora Ekana Nainggolan; Heri Pandapotan Silitonga; Debi Eka Putri (International Journal Of Community Service, 2023)
MSMEs are the foundation of the people's economy that supports the nation's economy. In Indonesia, MSMEs contribute a lot to the regional budget. The position of MSMEs is considered very significant because this sector is not only a source of livelihood, but also provides direct and indirect employment opportunities for people with relatively low levels of knowledge and skills. During Covid-19, MSMEs experienced a significant decline. Do not escape MSMEs in Pematangsiantar City. Many MSMEs are confused because their companies are hindered and cannot even develop. Globally, supply chains have weakened due to the impact of Covid-19 due to restrictions in several surrounding areas, commodity prices have fallen, and the possibility of a global economic crisis has increased. The urgency of carrying out this community service activity with the theme of the Workshop on Optimizing the Use of Social Media and the Importance of Financial Management for IKM/UKM Actors in Pematang Siantar City is to provide additional understanding and knowledge to IKM/UKM owners as well as strategies to increase turnover from sales made. The method used in carrying out this activity is through lectures and discussions related to the topic of service. The stages of implementing this event include opening and explaining social media that is often used by consumers, strategies for using social media, explaining the importance of financial management and existing financial reports for a business. After the community service activities are completed, follow-up interviews are conducted regarding the impact of the community service activities. In accordance with the results of the interviews, it is known that the understanding of SME/UKM actors regarding social media knowledge and financial management has increased by 90%.